Interhemispheric ionosphere-plasmasphere system shows a high sensitivity to the exospheric neutral hydrogen density: a caution of the global reference atmospheric model hydrogen density - Kotov, Dmytro; Richards, Phil G.; Reznychenko, Maryna; Bogomaz, Oleksandr; Truhlík, Vladimír; Nossal, Susan; Mierkiewicz, Edwin; Zhivolup, Taras; Domnin, Igor; Miyoshi, Yoshizumi; Tsuchiya, Fuminori; Kumamoto, Atsushi; et al. (Frontiers in Astronomy and Space Sciences, 2023)
This study explores the impact of the exosphere hydrogen (H) density on the ionosphere-plasmasphere system using a model whose key inputs are constrained by ionosphere observations at both ends of the magnetic field line with an L-value of 1.75 in the American longitudinal sector during a period with low solar and magnetic activities. This study is the first to be validated by ground-based and satellite data in the plasmasphere and both hemispheres. The main finding is that the entire ionosphere-plasmasphere system is very sensitive to the neutral hydrogen density in the lower exosphere. It was found that an increase in the H density by a factor of 2.75 from the commonly accepted values was necessary to bring the simulated plasma density into satisfactory agreement with Arase satellite measurements in the plasmasphere and also with DMSP satellite measurements in the topside ionospheres of the northern and southern hemispheres. A factor of 2.75 increase in the H density increases the simulated plasma density in the afternoon plasmasphere up to ~80% and in the nighttime topside ionosphere up to ~100%. These results indicate prominently that using the commonly accepted empirical model of the H density causes unacceptable errors in the simulated plasma density of the near-Earth plasma shells. We alert the space science community of this problem.